Relevansi Konsep Neurosains Spiritual Taufiq Pasiak terhadap Psikoterapi Sufistik - Hermala Fitriani; Abdullah, Zuhair (Journal of Sufism and Psychotherapy, 2021)
Taufiq Pasiak is an Indonesian neuroscientist who has succeeded in mapping the spiritual circuits in the brain when a person experiences spiritual experiences. Spiritual activity is a healing medium in the process of Sufistic psychotherapy to cure one's physical and mental illness. On that basis, this study aims to determine the concept of spiritual neuroscience according to Taufiq Pasiak's thoughts, and to find out the relevance of the spiritual neuroscience concept to the healing process in Sufistic psychotherapy. This research is a literature study. Data was collected using the documentation method. The main data sources come from books and works by Taufiq Pasiak, while the supporting data sources come from references that are relevant to the topic of discussion. The data that has been obtained is then analyzed using descriptive methods. The results of this study conclude that the concept of spiritual neuroscience according to Taufiq Pasiak is a study to see human spirituality from the perspective of health and medicine with a brain science approach. Taufik Pasiak succeeded in mapping the four components of the brain that work when a person performs spiritual activities known as neurospiritual operators (ONS). In addition, the results of this study indicate that there is a relevance between spiritual neuroscience and Sufistic psychotherapy in the form of remembrance activities, prayer, fasting, reading shalawat, and praying. When doing sufistic psychotherapy activities, there are brain circuits that work on the prefrontal cortex, association areas, limbic system, and autonomic nervous system which also affect health.